2011
DOI: 10.1103/physreva.83.023824
|View full text |Cite
|
Sign up to set email alerts
|

Cancellation of dispersion and temporal modulation with nonentangled frequency-correlated photons

Abstract: The observation of the so-called dispersion cancellation of paired photons is generally attributed to the presence of frequency entanglement between two frequency anticorrelated photons. In this paper, it is shown that by introducing the appropriate amount of chromatic dispersion or phase modulation between nonentangled photons, it is also possible to observe these effects. Indeed, it is found that the relevant characteristic required for the observation of dispersion cancellation or the cancellation of tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…This is closely related to the demonstration of the possibility of using thermal (or pseudothermal), and thus nonentangled, radiation for two-photon imaging experiments [41]. As was demonstrated in [15], entangled and non-entangled sources can show strikingly similar behaviors when traversing the same optical system, characterized by a particular transfer function, provided that certain properties of the frequency correlations between photons are the same for both sources.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This is closely related to the demonstration of the possibility of using thermal (or pseudothermal), and thus nonentangled, radiation for two-photon imaging experiments [41]. As was demonstrated in [15], entangled and non-entangled sources can show strikingly similar behaviors when traversing the same optical system, characterized by a particular transfer function, provided that certain properties of the frequency correlations between photons are the same for both sources.…”
Section: Discussionmentioning
confidence: 52%
“…In dispersion cancelation, an effect that is observed in the temporal domain, namely the broadening of the second-order correlation function of paired photons propagating in two different optical fibers, it was shown that it can be suppressed, provided that the group velocity dispersion parameters of both fibers are identical but opposite in sign, and the photons are entangled [12][13][14]. However, it has recently been demonstrated that such effects could also be produced by frequency-correlated photons, which nonetheless might be non-entangled [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This is the case, for instance, of two-photon lithography [26,27] and remote dispersion and temporal modulation cancellation [18,22,28,29]. In all these cases, classical and quantum sources share the same enabling characteristics (certain frequency correlations) that allow us the sought-after observation.…”
Section: Fig 1 (Color Online) (A)mentioning
confidence: 99%
“…Alternatively, a full quantum formalism might be used instead [18]. Let us consider the scheme of Fig.…”
mentioning
confidence: 99%
“…One approach that has proven fruitful for developing classical analogs of quantum technologies [24][25][26][27][28] is that of time reversal [12,[29][30][31]. Under this transformation, downconversion, which is exclusively quantum mechanical, can be replaced by second-harmonic generation, which is a classical process.…”
mentioning
confidence: 99%